If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-2.4=4x+4
We move all terms to the left:
3(x-2.4-(4x+4)=0
| 6s+3=57 | | 6d+18=30 | | 6(-6-5v)=86 | | m-32=-66 | | 7m-9=4 | | 8=y÷14 | | 1/5(r+0.5)+5.24=3/2r+7/10(r+2.2) | | 9y-5=15y-17* | | 69d+15=429 | | 15=x÷2 | | 8=14y | | 5c-6=2c+15 | | 4(5z-7)=88 | | 3(2x+4)=5(x+4) | | 14=8y | | 4x-2x+6=10x-2 | | 3z/10-5=-6 | | 2w+2(2w+3)=804 | | 6t+2=32 | | -9r=-7r+8 | | 16-4m=m | | 14d+45=101 | | -2.4=(x-70/10) | | 60+x+20=180 | | r-(-9)=3 | | b–7=24 | | 4=1/4x+2 | | 50=x×3 | | 5x^2-44x+120=-30x+11x | | (9x-7)=(7x+1) | | 165=(1/2)15h | | 20=150=x×3 |